2018
DOI: 10.1186/s12864-018-5338-x
|View full text |Cite
|
Sign up to set email alerts
|

Complex regulation of microRNAs in roots of competitively-grown isogenic Nicotiana attenuata plants with different capacities to interact with arbuscular mycorrhizal fungi

Abstract: BackgroundNicotiana attenuata is an ecological model plant whose 2.57 Gb genome has recently been sequenced and assembled and for which miRNAs and their genomic locations have been identified. To understand how this plant’s miRNAs are reconfigured during plant-arbuscular mycorrhizal fungal (AMF) interactions and whether hostplant calcium- and calmodulin dependent protein kinase (CCaMK) expression which regulates the AMF interaction also modulates miRNAs levels and regulation, we performed a large-scale miRNA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 90 publications
0
39
0
Order By: Relevance
“…In plants, miRNAs affect root physiology and, once released in extracellular vesicles, may even affect neighboring plants and fungi. 21 The idea that interspecies effects of miRNAs take place also in animals has been put forward as a hypothesis, 22 and preliminary evidence for their cross-species communication is emerging. 23 , 24 However, our understanding on cross-species effects of miRNAs is still sketchy and requires robust confirmation.…”
Section: Micrornas: Regulators Of Cellular Communicationmentioning
confidence: 99%
“…In plants, miRNAs affect root physiology and, once released in extracellular vesicles, may even affect neighboring plants and fungi. 21 The idea that interspecies effects of miRNAs take place also in animals has been put forward as a hypothesis, 22 and preliminary evidence for their cross-species communication is emerging. 23 , 24 However, our understanding on cross-species effects of miRNAs is still sketchy and requires robust confirmation.…”
Section: Micrornas: Regulators Of Cellular Communicationmentioning
confidence: 99%
“…After wild fires, N. attenuata germinates from long‐lived seed banks and establishes mono‐culture populations, while encountering several ecological challenges. The plant is colonized by AMF (Pandey et al, 2018 ) and is also attacked by pathogens such as Fusarium and Alternaria species (Schuck et al, 2014 ). Furthermore, N. attenuata faces an unpredictable attack by a diverse suite of herbivore species, which is thought to represent an important ecological challenge for this species; consequently, N. attenuata recruits several direct and indirect defenses (Baldwin, 2001 ; Navarro‐Quezada et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the composition and role of the RNA‐directed RNA polymerase (RdR), DCL, and AGO components of the smRNA machinery during adaptation to these natural challenges have also been studied (Navarro‐Quezada et al, 2020 ). The composition of miRNAs in N. attenuata's genome (Xu et al, 2017 ) and its reprograming during herbivore attack, pathogen infection, and AMF colonization are also known (Pandey et al, 2018 ; Pradhan et al, 2017 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, studies have shown that lncRNAs are involved in various biological processes, and the mechanisms of gene expression regulation mediated by lncRNAs can be roughly divided into the following three categories: (1) epigenetic modification, which involves regulation of downstream genes by histone modification (Gong and Maquat, 2011 ) and chromatin remodeling (Beniaminov et al, 2008 ; Zhao et al, 2008 ; Mercer et al, 2009 ); (2) transcriptional regulation, which involves effects on the transcription of protein-coding genes (upregulation or downregulation of the expression of the genes) via interactions with their promoters or transcription factors (Igor et al, 2007 ; Zhao et al, 2008 ; Jing et al, 2010 ); and (3) posttranscriptional regulation, which involves processing of lncRNAs into small RNAs such as siRNAs (Tiash and Chowdhury, 2018 ; Tsai et al, 2018 ) and miRNAs (Yuya et al, 2008 ; Annilo et al, 2009 ; Pandey et al, 2018 ) that function via complementary binding to coding gene transcripts. Recent research on lncRNAs has mainly concentrated on humans and mice.…”
Section: Introductionmentioning
confidence: 99%